Pemanfaatan Jerami Padi Sebagai Bahan Campuran Briket Biocoal: Analisis Karakteristik Fisik dan Laju Pembakaran Dibandingkan Briket Konvensional - Maktub, Zana Azalia; Tamrin, Tamrin; Lanya, Budianto; Kuncoro, Sapto (abe.fp.unila.ac.id, 2025)
This study aims to examine the effect of different percentages of rice straw as a blending material in biocoal briquettes on their physical properties and combustion performance. Four variations of rice straw content were used: 16%, 31.9%, 47.7%, and 63.7%. The results showed that briquette density decreased with higher rice straw content, from 765.13 kg/m³ at 16% to 466.34 kg/m³ at 63.7%. Mechanical strength also varied: tensile stress reached 100,109.99 N/m² at 16% and dropped to 85,480.03 N/m² at 63.7%, while compressive strength ranged from 71,902.06 N/m² to 62,909.68 N/m². Drop tests indicated that higher rice straw content generally reduced impact resistance. Combustion tests revealed that briquettes with higher rice straw content ignited faster and burned more quickly, with a maximum combustion rate of 2.81 g/min for the 63.7% mixture compared to 1.73 g/min for the 16% mixture. However, the calorific value decreased as rice straw percentage increased, from 4,968.53 kcal/kg to 4,011.97 kcal/kg, while moisture content rose from 26.40% to 37.93%. Analysis of variance (ANOVA) for combustion rate confirmed a significant effect of rice straw proportion (F = 10.93; BNT 5% = 0.2998). Compared to conventional briquettes, rice straw biocoal briquettes showed competitive combustion performance but slightly lower mechanical durability. This study demonstrates the potential of utilizing rice straw as an alternative biomass material to produce environmentally friendly biocoal briquettes with acceptable physical properties and enhanced combustion rates. Keywords: Biocoal briquettes, rice straw, density, tensile stress, compressive strength, combustion rate, calorific value.